if a= -9 and b=-6,show that (a-b) not equal (b-a)
Answers
Answered by
69
Answer:
(A-B)= (B-A)
= (-9-(-6)=(-6-(-9)
= -9+6= -6+9
= -3 = 3
: Both values are different
Answered by
2
Given,
a = -9
b = -6
To Prove,
(a-b) ≠ (b-a)
Solution,
Let (a-b) be equation 1 and (b-a) be equation 2
Putting values of a and b given in the question in equation 1,
Equation 1 ⇒ (a-b) = (-9) - (-6)
Equation 1 ⇒ (a-b) = (-9) + 6
Equation 1 ⇒ (a-b) = 6 - 9
Equation 1 ⇒ (a-b) = (-3)
Putting values of a and b given in the question in equation 2,
Equation 2 ⇒ (b-a) = (-6) - (-9)
Equation 2 ⇒ (b-a) = (-6) + 9
Equation 2 ⇒ (b-a) = 9 - 6
Equation 2 ⇒ (b-a) = 3
After solving equation 1 and equation 2, we know that 3 ≠ (-3)
Therefore, Equation 1 ≠ Equation 2
(a-b) ≠ (b-a)
Hence proved that (a-b) is not equal to (b-a).
Similar questions